HUBUNGAN PENGETAHUAN IBU TENTANG GIZI DENGAN ASUPAN ENERGI PADA ANAK STUNTING - Rudy Hartono; Husnal Ula; Sunarto Sunarto; Agustian Ipa (Media Kesehatan Politeknik Kesehatan Makassar, 2017)
Background The nutritional problem is essentially a public health problem that is influenced by many factors, therefore the prevention of nutritional problems can not be done by health approach but also involves other sectors such as education, religion and social. In school-age children need more energy and other nutrients such as energy, protein, calcium, fluorine and iron as the activity increases. Optimal child growth depends on the provision of nutrition with good quality and quantity as well as true. Method This research is descriptive approach with survey method that describes mother's knowledge and energy intake in child stunting Population in this research is all elementary school student of Inpres Sengka Regency of South Bontonompo Regency of Gowa. The sample of this research is class III student of class III and IV with Stunting of nutritional status A total of 26 people with measured amount of counted 62 people consisting of class III number of 11 people and IV as many as 15 people, the reason to choose class III and IV is because students Able To remember when they want direcall. Primary data consists of: a. Mother's knowledge variable is obtained from direct interview with respondent by using questionnaire instrument which contains question about causes of stunting and food energy source and so on. b. The variable of energy nutrient intake from child feeding habits (sample) was obtained from 2x 24 hour food recall interview method using 2x 24 hour food recall form. Assessment of nutritional intake by this method is done two days with a one-day measurement interval. Good nutrition intake if ≥ 77.0% of and less if <77.0% AKG. c. The stunting variable was obtained by using anthropometric measurements using the TB/U indicator, the sample is said to be stunting if z-score <-3.0 SD or z-score ≥ -3.0 SD s / d <-2.0 SD and not stunting if z -score ≥ -2 SD. Data types are numerical (quantitative) and data processing using statistical analysis. Data processing using computer by providing certain code which then processed with software (software) SPSS 13.0.  Secondary data includes geographic and demographic data obtained from research sites and related institutions. The age data was obtained by looking at the identity of the children taken from primary school staff teachers in Sengka Sub-district, Bontonompo District, South Gowa. Result  The results showed that the mother's knowledge about good nutrition as many as 5 people (19.2%) and less as many as 21 people (80.8%). For a good energy intake as much as 11 people (42.3%) and less as many as 15 people (57.7%). As for the knowledge of mother about nutrition with energy intake that is having good knowledge of nutrition and energy intake of 1 person (3,8%), good nutrition knowledge and energy intake less than 4 people (15,3%) while having knowledge Less and good energy intake as much 10 people (38,4%), knowledge of less nutrition and energy intake less than 11 people (53,8%) and value (p> α = 0,05) explained that there is no significant relationship between Mother's knowledge about nutrition and energy intake in elementary school stunting children. Conclusion: 1. Maternal knowledge about nutrition category less as many as 21 people (80,7%) and good as many as 5 people (19,23%). 2. Less energy intake in children Stunting as many as 15 people (57.7%), good as many as 11 people (42.3%). 3. There is no relationship between knowledge and energy intake